Direction of Trade Statistics Quarterly, June 2015. (Direction of Trade Statistics; June 2015, 2015)
This June 2015 issue of Direction of Trade Statistics Quarterly provide, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. Quarterly issues of this publication provide, for about 160 countries, tables with current data (or estimates) on the value of imports from and exports to their most important trading partners. In addition, similar summary tables for the world, industrial countries, and developing countries are included. The yearbook provides, for the most recent seven years, detailed trade data by country for approximately 184 countries, the world, and major areas. Reported data are supplemented by estimates whenever such data are not current or are not available in monthly frequency.